An efficient method for simultaneous species, individual, and sex identification via in‐solution single nucleotide polymorphism capture from low‐quality scat samples. (25th November 2021) - Parker, Lillian D.; Campana, Michael G.; Quinta, Jessica D.; Cypher, Brian; Rivera, Isabel; Fleischer, Robert C.; Ralls, Katherine; Wilbert, Tammy R.; Boarman, Ryan; Boarman, William I.; Maldonado, Jesús E.
Abstract: Understanding predator population dynamics is important for conservation management because of the critical roles predators play within ecosystems. Noninvasive genetic sampling methods are useful for the study of predators like canids that can be difficult to capture or directly observe. Here, we introduce the FAECES* method (Fast and Accurate Enrichment of Canid Excrement for Species* and other analyses) which expands the toolbox for canid researchers and conservationists by using in‐solution hybridization sequence capture to produce single nucleotide polymorphism (SNP) genotypes for multiple canid species from scat‐derived DNA using a single enrichment. We designed a set of hybridization probes to genotype both coyotes ( Canis latrans ) and kit foxes ( Vulpes macrotis ) at hundreds of polymorphic SNP loci and we tested the probes on both tissues and field‐collected scat samples. We enriched and genotyped by sequencing 52 coyote and 70 kit fox scats collected in and around a conservation easement in the Nevada Mojave Desert. We demonstrate that the FAECES* method produces genotypes capable of differentiating coyotes and kit foxes, identifying individuals and their sex, and estimating genetic diversity and effective population sizes, even using highly degraded, low‐quantity DNA extracted from scat. We found that the study area harbours a large and diverse population of kit foxes and a relatively smaller population of coyotes. By replicating our methods in the future, conservationists can assess the impacts of management decisions on canid populations. The method can also be adapted and applied more broadly to enrich and sequence multiple loci from any species of interest using scat or other noninvasive genetic samples.